Aminopeptidase N inhibitory peptides derived from hen eggs: Virtual screening, inhibitory activity, and action mechanisms. (October 2020) - Zhao, Wenzhu; Zhang, Dan; Yu, Zhipeng; Ding, Long; Liu, Jingbo
Abstract: Aminopeptidase N (APN) is an important zinc-dependent metalloproteinase expressed on cell surfaces. This study was done to find APN inhibitory peptides using virtual screening and molecular docking. Hen egg proteins were cleaved using pepsin and trypsin in silico to peptides of different lengths. Dipeptides and tripeptides are more easily absorbed in the gastrointestinal tract (GIT). The bioactivity, solubility, absorption, distribution, metabolism, excretion, and toxicity properties of the dipeptides and tripeptides were then predicted. APN was used as a molecular docking target for potential peptides. The tripeptides CNR, CDR and GEF were docked with the APN residues, His388, His392, Glu411, Glu355 and Tyr477. An in vitro APN inhibition assay showed that the IC50 values of CNR, CDR and GEF against APN were 8.94, 6.42, and 61.7 mM, respectively. Highlights: Three APN inhibitory peptides CNR, CDR, and GEF were identified. APN inhibition IC50 values of CNR, CDR, and GEF were 8.94, 6.42 and 61.7 mM, respectively. CNR, CDR, and GEF blocked APN using active sites and zinc-binding groups.